1993
DOI: 10.1121/1.406169
|View full text |Cite
|
Sign up to set email alerts
|

Sound localization in noise with hearing protectors: The effect of aging

Abstract: Sound localization ability was assessed in two groups of 24 normal-hearing subjects, aged 20–35 and 40–60 years. The test was conducted in a semi-reverberant chamber, using an array of six speakers, surrounding the subject at azimuth angles 60° apart, at a distance of 1 m. Three variables were investigated: the wearing of hearing protectors (unoccluded, conventional E-A-R plug and E-A-R muff, and Bilsom 2392 stereophonic muff with limited amplification), background (quiet vs 65 dB SPL white noise), and stimulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Localization performance was negatively affected by HPDs, with significant effects observed in the OTE and OTE-LPF listening conditions when compared to the NH condition. Previous studies have demonstrated increased localization errors with loss of spectral cues either through the use of a low-pass filter [ 60 62 ], or through the use of HPDs [ 6 , 11 , 13 , 14 , 37 , 39 ]. NIHL was simulated by removal of spectral information from the speech signals using a high order low-pass filter set at 2.5 KHz.…”
Section: Discussionmentioning
confidence: 99%
“…Localization performance was negatively affected by HPDs, with significant effects observed in the OTE and OTE-LPF listening conditions when compared to the NH condition. Previous studies have demonstrated increased localization errors with loss of spectral cues either through the use of a low-pass filter [ 60 62 ], or through the use of HPDs [ 6 , 11 , 13 , 14 , 37 , 39 ]. NIHL was simulated by removal of spectral information from the speech signals using a high order low-pass filter set at 2.5 KHz.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional passive HPDs, the most commonly used type of hearing protection, have been shown to reduce sound localization performance relative to unprotected ear (Berger, 2003;Berger & Casali, 1997;Bolia et al, 2001;Borg et al, 2008;Brungart et al, 2007;McKinley, 2000;Nixon & Berger, 1998;Noble et al, 1990;Simpson et al, 2005;Takimoto et al, 2007), and increase the number of front/back confusion errors (Abel & Armstrong, 1993;Abel & Hay, 1996;Alali & Casali, 2011;Brown et al, 2015;Gallagher et al, 2014, Gallagher et al, 2015a, Gallagher et al, 2015bZimpfer & Sarafian, 2014). In addition, earmuff-type devices are generally more detrimental to sound localization than earplugs (Abel & Hay, 1996;Russell, 1976;Suter, 1989;Talcott et al, 2012;Vaillancourt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%